Protocatechuic acid modulates hepatic oxidative stress and inflammation linked to DMN exposure in rat (Nigerian Journal of Physiological Sciences, 2023)
Dimethyl nitrosamine (DMN), a potent hepatotoxin, exerts carcinogenic effects and induces hepatic necrosis in experimental animals via CYP2E1 metabolic activation, and generation of reactive oxygen species (ROS). Protocatechuic acid (PCA), a plant-based simple phenolic compound and potent antioxidant, has been shown to affect the development of neoplasia in the rat liver and inhibit the initiation or progression phases of most cancers. In this study, the modulatory effects of PCA on DMN-induced hepatotoxicity, oxidative stress, inflammation, and selected phase I xenobiotic metabolizing enzymes were investigated in male Wistar rats. This study assessed biomarkers of hepatic injury (alanine transaminase, aspartate aminotransferase, alkaline phosphatase, and gamma- glutamyl transferase); oxidative stress (hydrogen peroxide concentration, lipid peroxidation, and reduced glutathione levels); measured activities of antioxidant enzymes (catalase, sodium dismutase, glutathione peroxidase, glutathione S-transferase); and inflammation (Tumor necrosis factor (TNF)-α, interleukin-1-Beta (IL-1β) and iNOS). The results of our investigation demonstrated that pretreatment with PCA at 50 and 100 mg/kg body weight p.o. reduced DMN (20 mg/kg bw) i.p. mediated hepatic injury, oxidative stress, and inflammation in a dose-dependent manner. In addition, the activities of phase I metabolizing enzymes were significantly induced except for aminopyrine-N-demethylase in the DMN-treated rats when compared with the DMN alone control group. This induction was also reversed by pre-treatment with PCA. The result of this study suggests that PCA is hepatoprotective against DMN-induced hepatic damage by its ability to suppress oxidative stress, inflammation, and modulate the activities of the selected phase I drug metabolizing enzymes. Thus, PCA may prove useful in combating DMN-induced hepatic damage
Keywords: Protocatechuic Acid; Hepatotoxicity; Antioxidant; Oxidative Stress; Dimethyl nitrosamine